Pemutusan Hubungan Kerja (PHK) Akibat Automasi dan Artificial Intelligence: Tantangan Hukum Ketenagakerjaan di Indonesia (International Forum of Researchers and Lecturers, 2025)
The rapid advancements in automation and artificial intelligence (AI) have significantly transformed various industries in Indonesia. While these technologies enhance efficiency and productivity, they also pose severe challenges to employment, notably the increasing prevalence of layoffs (PHK). This article critically analyzes the legal framework in Indonesia governing worker protection against layoffs caused by automation and AI. It highlights the inadequacies in current regulations, such as the Employment Law and the Job Creation Law, in addressing the unique challenges posed by digital transformation. Using a normative legal approach, the study emphasizes the need for adaptive policies, including reskilling, upskilling, and enhanced social security programs like the Employment Loss Insurance (JKP). Lessons from countries like Germany and Singapore underline the importance of government and industry collaboration in workforce readiness. The findings advocate for a holistic and inclusive policy framework to mitigate automation’s adverse effects while leveraging its potential for sustainable development.